The undercover economist - Harford, Tim, 1973- (Abacus, 2007)
Who makes most money from the demand for cappuccinos early in the morning at Waterloo Station? Why is it impossible to get a foot on the property ladder? How does the Mafia make money from laundries when street gangs pushing drugs don't? Who really benefits from immigration? How can China, in just fifty years, go from the world's worst famine to one of the greatest economic revolutions of all time, lifting a million people out of poverty a month?